Decision Support System for Selecting Outstanding Students University using the Method Multi Attribute Utility Theory (MAUT) - Achmad Fikri Sallaby (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The Selection of Outstanding Students describes the activities that have been carried out by the Higher Education since 2004. These activities include sorting and distributing awards to students who have achieved great achievements, both curricular and extracurricular achievements. Therefore, in each academy it is necessary to identify students who are able to do both and be given awards as outstanding students, namely by conducting mawapres selection at the high academic level. In the higher academies there is a program where students want to be selected and are also entitled to become outstanding students and are also given awards each year. In the process of achieving students at Budi Darma University, Medan, it is still being tried manually. This allows errors in the evaluation and processing of student data information. For this reason, it is necessary to make a decision support system that can help determine achievements and can take into account all the criteria. the predicate of outstanding students are cases that require an assessment process. So that in solving something that is needed a multi-process decision support system. The trick used in this research is the MAUT procedure. Determine the determination of students to overcome problems that require part of the evaluation process. So that the solution requires a multi-process decision support system. The procedure used in this research is the MAUT method. The MAUT method is to obtain a decision support information system for companies with a large level of data accuracy, so that by using this procedure it is expected to determine student achievement and process information more effectively. With this MAUT method creates the most preference as the best alternative results in the initial ranking which lies in the alternative with the highest preference level of 0.5419 on behalf of Khamsah Anugrah.